Review of State-Owned Banks in Belarus - World Bank (Washington, DC, 2014)
This note reviews state-owned banks in Belarus and offers recommendations on how to strengthen them. It covers the Belarusbank, Belagroprombank, Belinvestbank, and Paritetbank (the public banks), and the recently established Development Bank of Belarus (DBB). Recommendations focus on corporate governance, funding, ownership function, mandate, lending models, and regulation and supervision. The note is based on information provided by the public banks, the Ministry of Finance, and the NBRB. However, due to their unavailability, the team did not hold meetings with the DBB and the Ministry of Economy. Thus, the analyses concerning the DBB are based on the review of its law as well as on discussions with the Ministry of Finance and the NBRB. The note is organized as follows: after this introduction, section two presents an overview of the public banks in Belarus and the role that they play in the local economy; section three discusses the details of Lending under Government Programs (LGP) and the importance for the public banks of the funding attached to these programs; section four analyzes the key features of the DBB, offering recommendations on how strengthen it; and section five concludes.